Visualizing war emotions, technologies, communities - Engberg-Pedersen, Anders; Maurer, Kathrin (Routledge advances in art and visual studies ;, 2018)
Wars have always been connected to images. This book examines the emotional language of war images, how they entwine with various visual technologies, and how they can build emotional communities. From these different perspectives, the book provides a comprehensive overview of the nature and workings of war images from 1800 until today, and it offers a frame for thinking about the meaning of the images in contemporary wars.